Flex-rigid pleuroscopic biopsy with the SB knife Jr is a novel technique for diagnosis of malignant or benign fibrothorax - Wang, Xiao-Bo; Yin, Yan; Miao, Yuan; Eberhardt, Ralf; Hou, Gang; Herth, Felix; Kang, Jian (Journal of thoracic disease, 2016)
Diagnosing pleural effusion is challenging, especially in patients with malignant or benign fibrothorax, which is difficult to sample using standard flexible forceps (SFF) via flex-rigid pleuroscopy. An adequate sample is crucial for the differential diagnosis of malignant fibrothorax (malignant pleural mesothelioma, metastatic lung carcinoma, etc.) from benign fibrothorax (benign asbestos pleural disease, tuberculous pleuritis, etc.). Novel biopsy techniques are required in flex-rigid pleuroscopy to improve the sample size and quality. The SB knife Jr, which is a scissor forceps that uses a mono-pole high frequency, was developed to allow convenient and accurate resection of larger lesions during endoscopic dissection (ESD). Herein, we report two patients with fibrothorax who underwent a pleural biopsy using an SB knife Jr to investigate the potential use of this tool in flex-rigid pleuroscopy when pleural lesions are difficult to biopsy via SFF. The biopsies were successful, with sufficient size and quality for definitive diagnosis. We also successfully performed adhesiolysis with the SB knife Jr in one case, and adequate biopsies were conducted. No complications were observed. Electrosurgical biopsy with the SB knife Jr during flex-rigid pleuroscopy allowed us to obtain adequate samples for the diagnosis of malignant versus benign fibrothorax, which is usually not possible with SFF. The SB knife Jr also demonstrated a potential use for pleuropulmonary adhesions.
Gesehen am 05.06.2020